Criação de um training game: subsídios teóricos e práticos - Uribe, Maria Magdalena Vila (2012)
The growing usage of games in training and development area indicates that organizations demand for changes and new technologies capable of fostering an involving, pleasant and stimulating apprenticeship environment. Meanwhile, every day companies receive more and more collaborators who have grown up in a digital world, full of mobile electronic devices that allow the access to information anytime, anywhere. This dissertation has as its objective to examine both the theoretical and practical subsidies for the creation of a training game in this case, a corporative electronic game at distance modality and is based on a qualitative investigation (using specific bibliography) as well as on the experience of professionals who work in this area (obtained through interviews in order to know how they develop games). After an initial contextualization, the research presents a brief overview of the technological trends in education, the usage of games in corporate training and development area and aligns some of the concepts used in trainings, such as experience, group dynamics, play and game. After that, it refers to perception and interactivity aspects in teaching / learning scope according to the complex thought and investigates authors who deal with games creation, presenting the result of the investigation performed along with the developers of this kind of game in order to understand the market practices. The study of some theoretical and practical aspects for the creation of a training game allow us to understand important criteria in the development of this kind of game, such as how to invest in initial data survey, get to know many different games in order to widen up the view about mechanics and narratives, present a riveting challenge to the players, guarantee that the foreseen mechanics is able to achieve the pedagogical objective of the game and allow that the activity fosters moments of exploration and exchanges, stimulating the collaborative construction of knowledge